Comparison of Total Joint Replacement Rate Between Patients With Hemophilia A and Patients With Hemophilia B: A Population-Based and Retrospective Cohort Study. (December 2018) - Lin, Wen-Ya; Wang, Jiaan-Der; Tsan, Yu-Tse; Chan, Wei-Cheng; Tong, Kwok-Man; Chang, Shin-Tsu; Cheng, Yuan-Yang
Recurrent hemarthrosis in patients with hemophilia (PWH) results in chronic arthropathy requiring total joint replacement (TJR). This study aimed to compare the difference in TJR rate between patients with hemophilia A (HA) and hemophilia B (HB). A final total of 935 PWH (782 HA and 153 HB) without inhibitors were collected from the Taiwan's National Health Insurance Research Database between 1997 and 2013. Demographics, clinical characteristics, and TJR rate were compared between the 2 groups. The annual use of clotting factor concentrate was not different between HA and HB groups ( P = .116). The rate of comorbidities except for 29 PWH having HIV who were all in the HA group was also not different between the 2 groups. A total of 99 (10.6%) PWH had undergone 142 TJR procedures during the study period. All of them had received on-demand therapy. No difference was found in the cumulative incidence of TJR between HA and HB ( P = .787). After adjusting for various confounders including age, pyogenic arthritis, and HIV infection, no increased risk of TJR was found in patients with HA versus Patients with HB (hazard ratio: 0.92, 95% confidence interval 0.54-1.58). This finding suggests that the rate of TJR between patients with HA and HB is not significantly different.